The Influence of Drug-Polymer Solubility on Laser-Induced In Situ Drug Amorphization Using Photothermal Plasmonic Nanoparticles - Nele-Johanna Hempel; Padryk Merkl; Matthias Manne Knopp; Ragna Berthelsen; Alexandra Teleki; Georgios A. Sotiriou; Korbinian Löbmann (MDPI AG, 2021)
In this study, laser-induced in situ amorphization (i.e., amorphization inside the final dosage form) of the model drug celecoxib (CCX) with six different polymers was investigated. The drug-polymer combinations were studied with regard to the influence of (i) the physicochemical properties of the polymer, e.g., the glass transition temperature (Tg) and (ii) the drug-polymer solubility on the rate and degree of in situ drug amorphization. Compacts were prepared containing 30 wt% CCX, 69.25 wt% polymer, 0.5 wt% lubricant, and 0.25 wt% plasmonic nanoparticles (PNs) and exposed to near-infrared laser radiation. Upon exposure to laser radiation, the PNs generated heat, which allowed drug dissolution into the polymer at temperatures above its Tg, yielding an amorphous solid dispersion. It was found that in situ drug amorphization was possible for drug-polymer combinations, where the temperature reached during exposure to laser radiation was above the onset temperature for a dissolution process of the drug into the polymer, i.e., TDStart. The findings of this study showed that the concept of laser-induced in situ drug amorphization is applicable to a range of polymers if the drug is soluble in the polymer and temperatures during the process are above TDStart.